Components of a progressive reproductive management program - Stevenson, Jeffrey S. (Kansas Agricultural Experiment Station, 2011)
These are somewhat exciting times for dairy producers because of the new arsenal of hormones available for controlling estrous cycles and improving fertility. Using Bovilene® seems to assist cows in releasing a retained placenta. Most studies have demonstrated that using GnRH as a followup treatment (day 10 to 18 postpartum) for dairy cows with periparturient problems such as retained placenta improves their subsequent reproductive performance. Prophylactic treatment of early postpartum cows with GnRH (days 10 to 18) or prostaglandin F2alpha (days 20 to 40) improved their reproductive performance in most studies as well. Injections of GnRH at the time of insemination during late estrus in repeatservice cows effectively improves pregnancy rates. As with all new technologies and hormonal therapies, it is critical that attention be paid to consistent heat detection and good A.I. technique. Use of hormones will not replace, only supplement, good management procedures and common sense.
Keywords: Dairy; GnRH; Prostaglandins; Fertility; A.I.